Two-photon laser-assisted device alteration in CMOS integrated circuits using linearly, circularly and radially polarized light. (May 2016) - Rutkauskas, M.; Farrell, C.; Dorrer, C.; Marshall, K.L.; Crawford, T.; Lundquist, T.R.; Vedagarbha, P.; Erington, K.; Bodoh, D.; Reid, D.T.
Abstract: The rapidly developing semiconductor industry demands constant innovations in optoelectronic imaging of semiconductor integrated circuits to keep up with continuing device scaling. It was recently shown that two-photon laser-assisted device alteration (2pLADA) can deliver precision fault isolation. Here we describe an investigation into the influence of the incident light polarization on the 2pLADA spatial resolution. Linear polarization provides a highly confined but elliptical focal spot, while circular polarization diminishes the lateral resolution but benefits from a symmetrical focal spot. Radially polarized light potentially provides the highest lateral imaging resolution in all directions at the expense of the longitudinal resolution. By comparing 2pLADA results obtained using linear, circular and radial polarizations we show that certain polarizations have advantages in particular applications. Therefore a polarization optimized 2pLADA tool can achieve a sufficiently high performance to isolate faults of transistors separated by as little as 100 nm and maybe smaller. Graphical abstract: Highlights: two-photon laser-assisted device alteration provides precision fault localization in advanced integrated circuits spatial localization depends on the polarization state and the temporal overlap between the optical and electrical pulses linear polarization shows a clear advantage as long as the preferred polarization direction can be identified linear and radial polarizations provide better lateral localization resolutions than circular polarization radial polarization, while giving good localization, led to distortion, possibly due to the longitudinal E-field component